Development of a lexicon for red sufu. Issue 6 (27th July 2018) - He, Wenmeng; Chen, Yan Ping; Chung, Hau Yin
Abstract: Red sufu is a subtype of fermented soybean curd products that is red in color. There is little information available regarding the sensory properties of red sufu products. Therefore, the objectives of this investigation were to develop and validate a lexicon for profiling sensory properties of red sufu products. In this study, 10 qualified panelists were selected to develop a list of descriptors using 8 randomly selected commercial red sufus available from local market. M % value and principal component analysis (PCA) were used to reduce the number of descriptors from the initial 117 terms to the final 15 descriptors. Furthermore, 12 red sufu samples were selected for validation of the red sufu lexicon. Both PCA and agglomerative hierarchical cluster analysis validated that the newly developed lexicon could discriminate among red sufu samples. Practical applications: The lexicon developed in this study for red sufus will be useful for researchers and manufacturers to identify and describe similarities and differences of different commercial red sufus to help in their red sufu product development. Furthermore, it can be used to correlate with the instrumental data to strengthen the flavor quality control in the red sufu products.